Pengaruh Konsentrasi Awal Larutan terhadap Penyerapan Ion Logam Berat Cr3+ menggunakan Biomassa Alga Hijau Mougeotia sp. yang Dimodifikasi dengan Metanol - Hilmi Rahmadina; Mawardi Anwar (Jurnal Periodic Jurusan Kimia UNP, 2020)
Biosorption is an alternative method that can be used to overcome the presence of heavy metal chromium (III) in water. Green algae Mougeotia sp. Can be used as a biosorbent, because it has functional groups such as carboxyl, carbonyl, amine and hidroxyl. To find out how big the role of each functional group is modified. Where the functional group to be modified is the carboxyl group using methanol solution. In this research, the rebellion was carried out with a batch system, carried out by stirring the heavy metal solution with biosorbent then filtered, the resulting filtrate was analyzed using an Atomic Absorption Spectrophotometer (AAS). The variables to be tested is concentration. Based on the research results, the optimum absorption of green algae biomass Mougeotia sp. Against heavy metal ions Cr3+ took place at concentration of 250 mg/L with a maximum absorption capacity (qm) of 5.3050 mg/g. This biosorption process follows the Langmuir adsorption isotherm equation with an R2 value of 0.9412.